Development of a height estimation method based on the diameter at breast height of Prosopis alba Grisebach selected populations from a progeny trial in Santiago del Estero, Argentina - Frassoni, Javier Eduardo (2019)
Fil: Frassoni, Javier Eduardo. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias. Cátedra de Silvicultura; Argentina.